Modulation of Stem Cells as Therapeutics for Severe Mental Disorders and Cognitive Impairments - Zhang, Yongbo; Zhao, Yingying; Song, Xiaopeng; Luo, Hua; Sun, Jinmei; Han, Chunyu; Gu, Xiaohuan; Li, Jun; Cai, Guilan; Zhu, Yanbing; Liu, Zhandong; Wei, Ling; et al. (Frontiers in Psychiatry, 2020)
Severe mental illnesses (SMI) such as schizophrenia and bipolar disorder affect 2-4% of the world population. Current medications and diagnostic methods for mental illnesses are not satisfying. In animal studies, stem cell therapy is promising for some neuropsychiatric disorders and cognitive/social deficits, not only treating during development (targeting modulation and balancing) but also following neurodegeneration (cell replacement and regenerating support). We believe that novel interventions such as modulation of particular cell populations to develop cell-based treatment can improve cognitive and social functions in SMI. With pathological synaptic/myelin damage, oligodendrocytes seem to play a role. In this review, we have summarized oligodendrogenesis mechanisms and some related calcium signals in neural cells and stem/progenitor cells. The related benefits from endogenous stem/progenitor cells within the brain and exogenous stem cells, including multipotent mesenchymal-derived stromal cells (MSC), fetal neural stem cells (NSC), pluripotent stem cells (PSC), and differentiated progenitors, are discussed. These also include stimulating mechanisms of oligodendrocyte proliferation, maturation, and myelination, responsive to the regenerative effects by both endogenous stem cells and transplanted cells. Among the mechanisms, calcium signaling regulates the neuronal/glial progenitor cell (NPC/GPC)/oligodendrocyte precursor cell (OPC) proliferation, migration, and differentiation, dendrite development, and synaptic plasticity, which are involved in many neuropsychiatric diseases in human. On the basis of numerous protein annotation and protein-protein interaction databases, a total of 119 calcium-dependent/activated proteins that are related to neuropsychiatry in human are summarized in this investigation. One of the advanced methods, the calcium/cation-channel-optogenetics-based stimulation of stem cells and transplanted cells, can take advantage of calcium signaling regulations. Intranasal-to-brain delivery of drugs and stem cells or local delivery with the guidance of brain imaging techniques may provide a unique new approach for treating psychiatric disorders. It is also expected that preconditioning stem cell therapy following precise brain imaging as pathological confirmation has high potential if translated to cell clinic use. Generally, modulable cell transplantation followed by stimulations should provide paracrine protection, synaptic modulation, and myelin repair for the brain in SMI.